Proniosome: A Novel Non-ionic Provesicules as Potential Drug Carrier - Bachhav, Ashwini A. (Asian Journal of Pharmaceutics (AJP), 2016)
Vesicular systems are a novel means of drug delivery that can enhance the bioavailability of encapsulated drug and provide therapeutic activity in a controlled manner for a prolonged period of time. Liposomes were the first such system, but they suffer from a number of drawbacks including high cost and lack of stability at various pHs. To avoid the drawback of liposomes, niosomes were invented, which can be easily and reliably made in the laboratory. Niosomes are the ideal means of drug delivery that can enhance the bioavailability of encapsulated drug by various mechanisms and provide a therapeutic activity for a prolonged period of time. However, they suffer from aggregation, fusion, leaking, sedimentation of vesicles, and difficulty in sterilization; so to overcome these problems, a newer approach was employed which is known as pro-vesicular carriers. Here, in this review, we elaborate one of the pro-vesicular carriers, widely known as proniosome. This review covers all the aspects of proniosomes including mechanism, formulation variables and their effects, methods of preparation, parameters for characterizations, and application.